Production of conjugated linoleic acid by food-grade bacteria: a review - Andrade, José C. (2019)
Conjugated linoleic acid (CLA) is a group of isomers of linoleic acid (LA) with several potential health beneﬁts which justiﬁes the efforts to obtain foods with enhanced CLA contents. A possible way to obtain CLA-enriched products is via fermentation as several micro-organisms, many of which are employed in the manufacture of foods, are known to convert free LA into CLA. However, due to several constraints, the use of CLA-producing bacteria still remains challenging and continuous efforts are required. This review summarises the current knowledge on microbial CLA production by food-grade micro-organisms, its technical issues and limitations, potential applications and bioactivities.